Dual DNA binding specificity of ADD1/SREBP1 controlled by a single amino acid in the basic helix-loop-helix domain. - Kim, J B (1995)
Adipocyte determination- and differentiation-dependent factor 1 (ADD1), a member of the basic helix-loop-helix (bHLH) family of transcription factors, has been associated with both adipocyte differentiation and cholesterol homeostasis (in which case it has been termed SREBP1). Using PCR-amplified binding analysis, we demonstrate that ADD1/SREBP1 has dual DNA sequence specificity, binding to both an E-box motif (ATCACGTGA) and a non-E-box sequence previously shown to be important in cholesterol metabolism, sterol regulatory element 1 (SRE-1; ATCACCCCAC). The ADD1/SREBP1 consensus E-box site is similar to a regulatory sequence designated the carbohydrate response element, defined by its ability to regulate transcription in response to carbohydrate in genes involved in fatty acid and triglyceride metabolism in liver and fat. When expressed in fibroblasts, ADD1/SREBP1 activates transcription through both the carbohydrate response E-box element and SRE-1. Substitution of an atypical tyrosine in the basic region of ADD1/SREBP1 to an arginine found in most bHLH protein causes a restriction to only E-box binding. Conversely, substitution of a tyrosine for the equivalent arginine in another bHLH protein, upstream stimulatory factor, allows this factor to acquire a dual binding specificity similar to that of ADD1/SREBP1. Promoter activation by ADD1/SREBP1 through the carbohydrate response element E box is not sensitive to the tyrosine-to-arginine mutation, while activation through SRE-1 is completely suppressed. These data illustrate that ADD1/SREBP1 has dual DNA sequence specificity controlled by a single amino acid residue; this dual specificity may provide a novel mechanism to coordinate different pathways of lipid metabolism.